Does the relative age effect influence short-term performance and sport career in team sports? A qualitative systematic review - de la Rubia, A.; Lorenzo-Calvo, J.; Lorenz, A. (Frontiers in Psychology, 2020)
Background: The impact on athletes based on grouping methods according to the date of birth within the constituent year, known as the relative effect of age (RAE), is a factor that can influence the achievement of sports success. Many studies have examined the magnitude of this phenomenon in sport; however, the relationship between the RAE and performance in team sports competition has not been accurately evaluated so far. The purpose of this study was to conduct a systematic review on the influence of the RAE on competition performance in team sports through analysis of published peer-reviewed articles from 2000 to 2019.